PENDAMPINGAN GURU AGAMA ISLAM UNTUK MEWUJUDKAN INOVASI PENDIDIKAN BERBASIS TEKNOLOGI INKLUSIF - Ahmad Shofiyuddin; Ahmad Muthi’Uddin (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2024)
Abstract: Technology-based teaching modules are a form of teacher self-development in facing learning in the era of society 5.0. Creative and innovative teachers can create technology-based learning tools. Electronic teaching materials are in principle similar to manual teaching materials.He also describes Basic Competencies, Competency Achievement Indicators, practice question material. However, teaching materials based on Augmented Reality (AR) technology are more relevant because they are formatted with complete 3D images and visualization of the existing material.PKM activities are carried out for PAI teachers who are members of the PAI Subjects at 5 SMP/MTs institutions in Bojonegoro Regency with the aim of improving the abilities of PAI teachers and to increase the creativity of PAI teachers in developing PAI learning based on AR technology. PAI learning training uses AR-based modules. By carrying out this training, teachers can have new skills in creating learning media based on AR technology.